Pengaruh Jahe Merah Terhadap Nyeri Akut Pada Penderita Asam Urat Di Wilayah Kerja Puskesmas Cisaat - Hanti Marya Wanti; Lutiyah Lutiyah; Eva Martini (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Uric acid is a severe and painful form of joint inflammation, resulting from metabolic processes in the body due to the accumulation of crystals in the joints, leading to an increased level of uric acid in the body. The joints most commonly affected are the toes, knees, heels, wrists, fingers, and elbows. Acute pain in individuals with uric acid becomes a frequent issue, involving actual or potential tissue damage that can be described as ranging from mild to severe pain. Red ginger has various uses that can alleviate pain associated with joint pain or uric acid. The warm compress of red ginger helps improve blood circulation in the body and can also reduce pain. Objective: To determine the effect of red ginger compress on acute pain in patients with acute uric acid in the Cisaat Health Center's working area. Method: The design in this study uses Quasi-experimental with a one-group pretest-posttest design approach. The total population in this study is 96 people, with a sample size of 16 respondents selected using purposive sampling. Data analysis was conducted using the Paired T-test. Results: The results of the statistical test with the Paired Samples Test showed a P-value of 0.000 < 0.05. There is an influence of red ginger on acute pain in patients with uric acid in the Cisaat Health Center's working area